Internação provisória, liberdade assistida e jovens assassinados: existências interrompidas por um itinerário penalizador - Lima, Cezar Bueno de (2007)
The institutional determinations about juvenile delinquents who spent some time in the tutelary and attendance complex in Londrina (PR.), including those who were murdered, constitute the study object of this thesis. The purpose of the research was to analyze the penalizing route prior to those youngsters death, focusing on the practices of social and juridical technicians working in institutions responsible for these youngsters provisional internment, judicial sentence and follow-up of social-educational measures outside the institutions. The data gathering and the record analysis carried out together with the project Murialdo, the Integrated Center for the Attendance of the Juvenile Delinquent (CIAADI/SAS) and the Infancy and Juvenile Jurisdiction of the Forum of Londrina Pr., made it possible to obtain information and analyze the processes to discuss the selectivity of the juvenile penal justice, the negative figure of crime and the regularity of the penalizing discourse among agents authorized to deal with juvenile delinquents, and those who were exterminated during the period they were carrying out social-educational measures outside the institutions. The analytical issue of the research asks to what extent the adoption of juridical-political measures of juvenile control from a distance represent the continuity of official penalizing solutions, based on academic-discourse practices with the purpose of extending the mechanisms of control, life management and continuous reinforcement of the State power. Against this, the thesis intends to criticize the model of action of the juvenile control apparatus and stimulate changes of attitude that call the attention to the existence of a society without penalties and make it viable, apart from the State penal justice apparatuses, the creation of conflicts solution mechanisms which grant power to the parts directly and indirectly involved, to solve the problems where they occur